2018
DOI: 10.1002/jcp.27768
|View full text |Cite|
|
Sign up to set email alerts
|

Clusterin enhances AKT2‐mediated motility of normal and cancer prostate cells through a PTEN and PHLPP1 circuit

Abstract: Clusterin (CLU) is a chaperone‐like protein with multiple functions. sCLU is frequently upregulated in prostate tumor cells after chemo‐ or radiotherapy and after surgical or pharmacological castration. Moreover, CLU has been documented to modulate the cellular homolog of murine thymoma virus akt8 oncogene (AKT) activity. Here, we investigated how CLU overexpression influences phosphatidylinositol 3′‐kinase (PI3K)/AKT signaling in human normal and cancer epithelial prostate cells. Human prostate cells stably t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The CLU encoding protein is a secreted chaperone that can be found in the cell cytosol under stress conditions. CLU is involved in basic BPs, such as cell death, neurodegenerative disorder, and tumor progression (Bertacchini et al, 2019;Seo et al, 2019). Previous studies also demonstrated that the CLU protein can interact with HSP90AA1 and enhance the effect of HSP90AA1 on the activation of the Eph receptor B1 (ERK), AKT serine/threonine kinase 1 (AKT), and nuclear factor kappa B (NF-κB) families, in addition to epithelial-tomesenchymal transition and migration in breast cancer cells (Tian et al, 2019).…”
Section: Cross-species Analysis Of Candidate Genesmentioning
confidence: 99%
“…The CLU encoding protein is a secreted chaperone that can be found in the cell cytosol under stress conditions. CLU is involved in basic BPs, such as cell death, neurodegenerative disorder, and tumor progression (Bertacchini et al, 2019;Seo et al, 2019). Previous studies also demonstrated that the CLU protein can interact with HSP90AA1 and enhance the effect of HSP90AA1 on the activation of the Eph receptor B1 (ERK), AKT serine/threonine kinase 1 (AKT), and nuclear factor kappa B (NF-κB) families, in addition to epithelial-tomesenchymal transition and migration in breast cancer cells (Tian et al, 2019).…”
Section: Cross-species Analysis Of Candidate Genesmentioning
confidence: 99%
“…PI3K works as an extracellular sensor, and, through the binding of growth factors, activates Akt, the effector of the pathway [ 28 , 29 ]. The PI3K/Akt pathway exerts several pro-tumorigenic functions, through interaction with cellular proteins acting as cell cycle modulators, anti-apoptotic and transcriptional factors (TFs) [ 30 ]. We confirmed that Akt itself and several downstream effectors were indeed highly phosphorylated in C91/III cells ( Figure 1 ), and that the HFF coculture was inducing the same profile of PI3K/Akt hyperactivation in the parental C91/PL cells, suggesting that crosstalk with the microenvironment can promote a pro-survival phenotype in lymphomatous cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-190-5p functioned as a tumor suppressor in one study about HCC [19], whereas it functioned as an oncogene in another study about HCC [30]. Similarly, miR-190-5p suppresses prostate cancer proliferation [21], while it promotes cell migration and invasion in another study on prostate cancer [29]. If each study is scientific and convincing, we assume that the differences might be associated with different cancer cell lines used or experimental methods employed.…”
Section: Discussionmentioning
confidence: 99%
“…Clusterin, a small heat-shock-like protein, is overexpressed in many solid tumors and regulates the PI3K/AKT pathway. Clusterin was shown to dramatically enhance the migratory and invasive behavior of the normal prostate epithelial cell line PNT1A and the prostate cancer cell line PC3 by regulating the miR-190-5p-PHLPP1 axis, suggesting that miR-190-5p functions as an oncogene in prostate cancer [29]. Furthermore, miR-190-5p promotes cell migration and invasion by targeting FOXP2 in gastric cancer [18], suggesting a differential function of miR-190-5p possibly related to the specific disease context.…”
Section: Mir-190-5p In Cancer Development and Progressionmentioning
confidence: 99%